2021
DOI: 10.1371/journal.pone.0251032
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised tensor decomposition-based method to extract candidate transcription factors as histone modification bookmarks in post-mitotic transcriptional reactivation

Abstract: The histone group added to a gene sequence must be removed during mitosis to halt transcription during the DNA replication stage of the cell cycle. However, the detailed mechanism of this transcription regulation remains unclear. In particular, it is not realistic to reconstruct all appropriate histone modifications throughout the genome from scratch after mitosis. Thus, it is reasonable to assume that there might be a type of “bookmark” that retains the positions of histone modifications, which can be readily… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Here, we used a data-driven approach based on TD as a multivariate analysis method applied to multi-omics datasets. TD enables data-driven analyses such as data dimensionality reduction, classification, and potential FE [9,10] and has been widely applied to omics studies [3,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Omberg et al integrated genome-scale mRNA expression data from three cell cycle time courses in yeast to identify genes and the differential effects of gene-mediated biological processes on cell cycle progression using TD.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used a data-driven approach based on TD as a multivariate analysis method applied to multi-omics datasets. TD enables data-driven analyses such as data dimensionality reduction, classification, and potential FE [9,10] and has been widely applied to omics studies [3,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Omberg et al integrated genome-scale mRNA expression data from three cell cycle time courses in yeast to identify genes and the differential effects of gene-mediated biological processes on cell cycle progression using TD.…”
Section: Introductionmentioning
confidence: 99%
“…Cell division involves the division of one cell into two genetically identical daughter cells, and is tightly controlled during differentiation processes. During the cell-division process, gene transcription must be initially terminated and then reactivated once cell division is complete ( Taguchi and Turki 2021 ). DNA replication determines the timing of mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used a data-driven approach based on TD as a multivariate analysis method applied to multi-omics datasets. TD enables data-driven analyses such as data dimensionality reduction, classification, and potential FE (9,10) and has been widely applied to omics studies (Alter and Golub, 2005 Yahyanejad, 2019 (7,(11)(12)(13)(14)(15)(16). Omberg et al (2007) integrated genome-scale mRNA expression data from three cell cycle time courses in yeast to identify genes and the differential effects of gene-mediated biological processes on cell cycle progression using TD.…”
Section: Introductionmentioning
confidence: 99%
“…TD also has been applied to analyses within each omics (1721) and among multiple omics (3,22,23). Recently, the application of TD-based unsupervised FE was proposed (Taguchi, 2017a, 2017b, 2017c; Taguchi and Turki, 2019, 2021; Taguchi, 2020). Taken together, the data-driven analyses using TD in these studies have shown that biologically meaningful features can be extracted by a data-driven non-biased method from datasets with various modes.…”
Section: Introductionmentioning
confidence: 99%